Status of immunity against poliomyelitis: a study among european and extra-european young immigrants living in Parma - Affanni, P.; Veronesi, L.; Rizziero, et al., S. (Acta Biomedica Atenei Parmensis, 2005)
From January 2001 to December 2003 blood specimens obtained from 323 European and extra-European young immigrants were collected for the determination of anti-polio antibody levels. They were sent to the Section of Hygiene, Department of Public Health, by the Local Health Authorities. A neutralization assay was performed to detect the anti-polio antibodies against serotypes 1, 2 and 3, using rhesus monkey kidney cells. The results showed 98,1% prevalence of anti-polio 1 antibodies (titre ≥1:2), 99,1% of anti-polio 2, and 98,8% prevalence of anti-polio 3 antibodies. The seronegativity against only one or two serotypes (antibody titre <1:2) was found in 9 subjects (2,8%) while no subject was found totally seronegative against all 3 serotypes. According to the total amount of the analyzed samples, the estimated Geometric Mean Titre (GMT) resulted from moderate to low (GMT=29 of serotype 3; GMT=48,4 of serotype 2; GMT=56,5 of serotype 1) and it appeared to be similar to the results obtained in the previous years for all 3 serotypes; the GMT of serotype 3 was still the lowest. No difference was observed in the specimens with respect to the country of origin of the examined subjects and the data collected showed a good level of immunity.